A comparative study of MassARRAY and GeneXpert assay in detecting rifampicin resistance in tuberculosis patients’ clinical specimens - Liang, Ruixia; Li, Jiankang; Zhao, Yue; Qi, Haoran; Bao, Shengjuan; Wang, Fen; Duan, Hongfei; Huang, Hairong (Frontiers in Microbiology, 2024)
Objectives: Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) has emerged as a potent tool for detecting drug resistance in tuberculosis (TB); however, concerns about its reliability have been raised.In this study, we assessed the reliability of MassARRAY (Sequenom, Inc.), which is a MALDI-TOF MS based method, by comparing it to the well-established GeneXpert assay (Cepheid) as a reference method.Methods: A retrospective study was conducted using laboratory data retrieved from Henan Chest Hospital (Zhengzhou, China). To ensure a rigorous evaluation, we adopted a comprehensive assessment approach by integrating multiple outcomes of the Xpert assay across various specimen types.Results: Among the 170 enrolled TB cases, MassARRAY demonstrated significantly higher sensitivity (85.88%, 146/170) compared to the Xpert assay (76.62%, 118/154) in TB diagnosis (P<0.05). The concordance in detecting rifampicin resistance between MassARRAY and the combined outcomes of the Xpert assay was 90%, while it was 97.37% (37/38) among smear-positive cases and 89.06% (57/64) among culturepositive cases. When compared to the phenotypic susceptibility outcomes of the 12 included drugs, consistency rates of 81.8% to 93.9% were obtained, with 87.9% for multiple drug-resistance (MDR) identification.Conclusions: MassARRAY demonstrates high reliability in detecting rifampicin resistance, and these findings may offer a reasonable basis for extrapolation to other drugs included in the test panel.